2009
DOI: 10.1161/hypertensionaha.108.122333
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Experimental Severe Cardiac Fibrosis Is Mediated by Overexpression of Angiotensin-Converting Enzyme 2

Abstract: Abstract-Angiotensin-converting enzyme (ACE) 2 is a recently identified homologue of ACE. There is great interest in the therapeutic benefit for ACE2 overexpression in the heart. However, the role of ACE2 in the regulation of cardiac structure and function, as well as maintenance of systemic blood pressure, remains poorly understood. In cell culture, ACE2 overexpression led to markedly increased myocyte volume, assessed in primary rabbit myocytes. To assess ACE2 function in vivo, we used a recombinant adeno-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Thus, the beneficial effects of ACE2 observed in this study are most likely attributable to the net effect of decreased local Ang II level and increased local Ang-(1-7) level. Recent studies found that long-term ACE2 overexpression or Ang-(1-7) injection accelerated myocardial fibrosis or diabetic nephropathy (7,39,40). In this study, the outcome of ACE2 overexpression was assessed 4 weeks after gene transfer, and no detrimental effects were found, suggesting that our gene therapy offers a safe approach.…”
Section: A C E 2 -A M E L I O R a T E D D I A B E T I C N E P H R O Pmentioning
confidence: 70%
“…Thus, the beneficial effects of ACE2 observed in this study are most likely attributable to the net effect of decreased local Ang II level and increased local Ang-(1-7) level. Recent studies found that long-term ACE2 overexpression or Ang-(1-7) injection accelerated myocardial fibrosis or diabetic nephropathy (7,39,40). In this study, the outcome of ACE2 overexpression was assessed 4 weeks after gene transfer, and no detrimental effects were found, suggesting that our gene therapy offers a safe approach.…”
Section: A C E 2 -A M E L I O R a T E D D I A B E T I C N E P H R O Pmentioning
confidence: 70%
“…These studies suggest a protective role for ACE2 in cardiac remodelling through reduced AngII production. However, other studies have shown the opposite in that overexpression of ACE2 is potentially associated with a worsened cardiac phenotype [48,49]. This phenomenon could be due to supraphysiological levels of expression at specific unwanted sites and therefore further studies are required to address this conflicting data.…”
Section: The Counter Regulatory Axis Of the Ras In Cardiac Remodellingmentioning
confidence: 97%
“…8 Despite these research efforts, several key issues remain unsolved. First, because the half-life of Ang-(1-7) in vivo is very short 9 and a large dose of Ang-(1-7) may cause adverse effects, 10 the dose-response relationship between Ang-(1-7) and early atherosclerotic lesions needs to be clarified. Second, it is unclear whether Ang-(1-7) is capable of inhibiting early atherosclerotic lesion formation and stabilizing mature atherosclerotic plaques.…”
mentioning
confidence: 99%